Reinterpreting Brand Experience Stimuli through Virtual Space Avatars and Metaverse Co-Creation - Aziz, Caesar Achmad Firjaun Faqih; Grahita, Banung (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2025)
The transformation of digital spaces into three-dimensional virtual ecosystems, widely known as the metaverse, has fundamentally reshaped the paradigm of brand experience from traditional visual narrative communication into participatory, immersive, and multisensory engagement. This study aims to reinterpret and extend the conventional understanding of brand experience by identifying the key stimuli that shape user interactions within virtual environments. Employing a qualitative exploratory approach based on the AEIOU framework (Activities, Environments, Interactions, Objects, and Users) and reflective thematic analysis, the research examined eight major metaverse platforms across five categories: game-based, social playground, VR-based, NFT-based, and event-based. The analysis revealed five primary dimensions that collectively construct brand experience in the metaverse: immersive presence, virtual space, avatar-mediated interaction, personalized virtual goods, and dynamic co-creation. These dimensions redefine the brand experience from a stimulus–response perspective into a participatory, socially driven relationship in which users actively co-create meaning, identity, and value with brands. The findings highlight how digital stimuli and multisensory interactions within metaverse spaces foster emotional attachment and brand engagement, offering both conceptual and managerial implications. From a theoretical standpoint, this research provides an initial framework for understanding brand experience in immersive digital environments, while practically, it guides marketers and brand strategists to design interactive, personalized, and community-oriented branding initiatives. Ultimately, the study opens new opportunities for future research to empirically examine the link between metaverse-based experiences, user perception, and brand outcomes such as trust, attachment, and loyalty within the evolving digital ecosystem.